Scatterplot Variations Seen in Malaria Using Automated Hematological Analyzers: A Series of Ten Cases - Ronit Juthani; Tavish Gupta; Debdatta Basu (University Library System, University of Pittsburgh, 2021)
Background: Malaria is a major health problem in India. Complete blood count and peripheral blood smear (PBS) is important for its diagnosis. Inter observer variation makes PBS fallible. Rapid diagnostic tests cannot detect low parasitemia and mixed infections. Scatterplot from automated analyzers have shown variations previously which might be exploited. Methods: Scatterplot patterns of ten samples of confirmed malaria and 100 control samples were derived and other infections ruled out by culture and serology as a part of descriptive study between July and August 2018. Each malarial scatterplot was compared with the control pattern for abnormalities and their frequency noted. Results: All the ten samples belonged to Plasmodium vivax species. Abnormalities detected included split in neutrophilic region, eosinophil-neutrophil merge, neutrophil graying, lymphopenia, ghost red blood cells (RBC), eosinophil split, reactive lymphocytes, monocytosis, pseudoeosinophilia, neutrophilic leukocytosis Conclusion: Variations in scatterplot patterns are seen in malaria and provide clues to the diagnosis of malaria.